Design of 0–3 type nanocomposites using hydrothermal sintering. (15th April 2018) - Ndayishimiye, Arnaud; Buffière, Sonia; Dourges, Marie-Anne; Largeteau, Alain; Prakasam, Mythili; Mornet, Stéphane; Kaman, Ondřej; Zdenĕk, Jirák; Hejtmánek, Jiří; Goglio, Graziella
Abstract: We report here the successful design of 0–3 type nanocomposites where 30 nm ferromagnetic metallically conducting cores of manganite La0.66 Sr0.34 MnO3 (LSMO) are discretely distributed in an insulating silica matrix. Starting from LSMO@SiO2 core@shell nanoparticles, hydrothermal sintering process was used as a low temperature densification route (300 °C, 350 MPa, 90 min) in presence of 0.2 M aqueous sodium hydroxide solution. This process based on a pressure solution creep in the contact zones between nanoparticles allows the design of complex microstructures preventing the grain growth of the cores and the formation of interphases between the cores and the matrix. Graphical abstract: Unlabelled Image